Injury epidemiology in para alpine skiing: insights from three paralympic winter games (2014-2022) - Derman, W.; Runciman, P.; Boer, P.; Dahlin, K.; Johansson, M.; Lexell, J.; Fagher, K. (BMJ Open Sport & Exercise Medicine, 2026)
Introduction High injury rates have been reported in Para Alpine skiing at the Winter Paralympic Games, yet sport-specific injury characteristics remain limited. This study aimed to describe the proportion and incidence of injuries among athletes competing in Alpine skiing at the Sochi 2014, PyeongChang 2018, and Beijing 2022 Games, and to examine injuries by sex, age, impairment type, competition period, onset, anatomical area, and estimated time-loss burden.